The Influence of English Ability and Educational Methods on the Military Vehicles Operationalization for Cadets in the Army and Military Academy at Cavalry Educational Center, Padalarang, Indonesia - Fauziyah Aulia Rishanti (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2021)
English skills are needed in the military field which always faces dynamic conditions. This research was intended to determine the relationship between English ability and educational methods used by military cadets at the Pusat Pendidikan Kavaleri on their ability to operate military vehicles. The method used is a quantitative method with population were all Army Secapa cadets and the Indonesian Army Military Academy who were currently studying at the Cavalry Education Center (Pusdik Kav) in Padalarang, West Java Province, Indonesia. Data collection technique used was observational technique, which was to examine directly by using a questionnaire and interview. The result of this research is that there is a significant relationship between the English Ability and the Educational method on military vehicles operationalization. In other words, if the English Ability and the Educational method is increased, the military vehicles operationalization for the Indonesian Army will be greater. In addition, the findings of this research are useful for military cadets and institution itself.